MPMH 21 pearl millet for drought prone areas - Rajpurohit, B. S.; Yadav, O. P.; Beniwal, B. R.; Bishnoi, H. R.; Kumar, Manoj; Meena, R. C. (Indian Farming, 2018)
In vast majority of pearl millet growing north-west regions, existing crop-livestock farming system is the basis of food and fodder security. In these regions, drought is the most important production constraint. Hence, early maturing and dualpurpose cultivars providing both high grain and fodder are preferred. The MPMH 21 pearl millet is one such new hybrid. Bred at the All India Coordinated Research Project (AICRP) on Pearl millet, using malesterile line ICMA 93333 pearl millet and restorer MIR 524 pearl millet, MPMH 21 pearl millet established its superiority to two checks viz., RHB 177 and HHB 67 improved during kharif at 34 locations for its performance with respect to grain yield, stover yield and disease resistance. The hybrid MPMH 21 pearl millet provided 10-28% higher grain yield than two national checks. Similarly, the dry stover yield of MPH 21 pearl millet was also 17-23% higher than the check hybrids. Another distinctive advantage of MPMH 21 pearl millet was high degree of resistance to downy mildew and blast. The hybrid MPMH 21 pearl millet matures within 75 days. The very attractive phenotypic appeal with complete exertion of panicle in MPMH 21 pearl millet is another uniqueness of this hybrid. High tillering capacity of hybrid also helps in adaptation to mid-season drought spells. Hybrid can be easily identified by its unique traits. Grains contain, on an average, 11% protein, 6.2% fat, 41 ppm iron and 35 ppm zinc(Zn).